2019
DOI: 10.21272/mmi.2019.3-12
|View full text |Cite
|
Sign up to set email alerts
|

Market Segmentation in Healthcare

Abstract: The share of healthcare expenditure in the first income decile in their income is higher in comparison with other deciles, however, their expenditure is the lowest. The main purpose of the research is to show the availability of healthcare in different income groups of households. Literature sources indicate that some specific household social classes face problems with access to healthcare because of low income. Firstly, public healthcare expenditure is evaluated. The low share of research and development exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Sterck et al (39) derived a health poverty line based on basic health care costs and health spending at 5% of income. Antosova et al (40) constructed a health poverty index to show how much money households lack to meet prescribed standards of health care. Beyond that, CHE is a more commonly used and widely accepted indicator in the international health economy to measure the economic risk of poor health, which is defined as out-of-pocket health care expenditure that exceeds a certain percentage of household income and imposes a disease burden on the household (11,41,42).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Sterck et al (39) derived a health poverty line based on basic health care costs and health spending at 5% of income. Antosova et al (40) constructed a health poverty index to show how much money households lack to meet prescribed standards of health care. Beyond that, CHE is a more commonly used and widely accepted indicator in the international health economy to measure the economic risk of poor health, which is defined as out-of-pocket health care expenditure that exceeds a certain percentage of household income and imposes a disease burden on the household (11,41,42).…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is also necessary to consider the multilevel measurement of socio-economic determinants (Druzhynina et al, 2018;Kyrychenko et al, 2018) and the existing relationship (Halaskova & Bednar, 2020;Luchko, 2019;Pupavac et al, 2020). Antosova et al (2019) and Baranowski & Jabkowski (2021) identify indicators depending on household income clusters. The trend of economic growth, population health and environmental indicators are directly related to the consequences of blocking the pandemic (Smiianov et al, 2020a;Petrushenko et al, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thus, it was revealed that for the insurance company, the main pluses in the running of virtual business could be: lower costs concerning the organization of the company's website; fewer costs concerning the transactions for customer service operations; «expansion of geographical diversification of company insurance products; an opportunity to increase the sale of insurance products at the expense of open access to customers from around the world; customer service on a qualitatively new level -seven days a week, 365 days a year» (Yanyshyn et al, 2019). There was also paid great attention for the research that showed the presence of healthcare in special households' groups, the way of accelerating the transformation of the management process with human resources, as well as the adequate assessment of the countries' investment potential in the content of health insurance was also deeply investigated (Antosova et al, 2019;Kasaeva, 2019). Zhang (2011) underlines that the favorable factors for the development of old-age care insurance include the aging population trend, the rising nursing costs, the high burden of the elderly, the high medical costs, and the lack of medical securityю Moreover, He and Li (2014) assessed the payment capacity of farmers; Sheng et al (2020) studied the pilot system and current situation of long-term care insurance and put forward corresponding suggestions in Suzhou.…”
mentioning
confidence: 99%